2021
DOI: 10.1007/s00405-021-06992-2
|View full text |Cite
|
Sign up to set email alerts
|

Status quo after one year of COVID-19 pandemic in otolaryngological hospital-based departments and private practices in Germany

Abstract: Purpose The COVID-19 pandemic has affected healthcare systems worldwide. Data on the impact on otolaryngological clinics and private practices is sparse. This study aimed to present data on healthcare worker (HCW) screening, status of HCW, pre-interventional testing, the use of personal protective equipment (PPE) and the economic impact of the pandemic. Methods Otolaryngological private practices and hospital-based departments were surveyed nationwide using an online questionnaire. Participating facilities wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…As it is a continuation of the CoREM-NUM study, the objective focuses on risk assessment of aerosol-generating procedures in the context of the COVID-19 pandemic. Details and results on the first part of the CoREM-NUM study were reported in previous publications [ 10 , 11 , 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…As it is a continuation of the CoREM-NUM study, the objective focuses on risk assessment of aerosol-generating procedures in the context of the COVID-19 pandemic. Details and results on the first part of the CoREM-NUM study were reported in previous publications [ 10 , 11 , 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%